2020
DOI: 10.3390/cancers12061646
|View full text |Cite
|
Sign up to set email alerts
|

COX5B-Mediated Bioenergetic Alteration Regulates Tumor Growth and Migration by Modulating AMPK-UHMK1-ERK Cascade in Hepatoma

Abstract: The oxidative phosphorylation machinery in mitochondria, which generates the main bioenergy pool in cells, includes four enzyme complexes for electron transport and ATP synthase. Among them, the cytochrome c oxidase (COX), which constitutes the fourth complex, has been suggested as the major regulatory site. Recently, abnormalities in COX were linked to tumor progression in several cancers. However, it remains unclear whether COX and its subunits play a role in tumor progression of hepatoma. To search for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…An increasing body of evidence from recent decades has supported that bioenergetic homeostasis is crucial for tumorigenesis and/or the progression of many cancer types, including HCC and CRCs [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 24 ]. COX5B has been reported as a growth-promoting gene that modulates downstream pathways in response to the induced bioenergetic alterations in HCC, breast cancer, and glioma, but its role in CRCs remains unknown [ 24 , 29 , 30 , 31 ]. As such, clinical associations and experimental assays were conducted to investigate the role and potential mechanism of action of COX5B in CRCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing body of evidence from recent decades has supported that bioenergetic homeostasis is crucial for tumorigenesis and/or the progression of many cancer types, including HCC and CRCs [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 24 ]. COX5B has been reported as a growth-promoting gene that modulates downstream pathways in response to the induced bioenergetic alterations in HCC, breast cancer, and glioma, but its role in CRCs remains unknown [ 24 , 29 , 30 , 31 ]. As such, clinical associations and experimental assays were conducted to investigate the role and potential mechanism of action of COX5B in CRCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two distinct reference datasets were comparatively analyzed, which revealed that several subunits of COX were significantly elevated or downregulated in HCC. Only COX subunit 5B (COX5B) harbored an oncogene-like property, as HCC patients with higher COX5B expression showed poorer clinical outcomes [ 24 ]. Moreover, a signaling cascade composed of AMPK-UHMK1-ERK operating through COX5B-mediated bioenergetic alterations was also demonstrated, and further reinforcing the hypothesis that COX5B has an oncogene-like property.…”
Section: Introductionmentioning
confidence: 99%
“…COX5B gene encodes cytochrome c oxidase, and it is another critical component of the mitochondrial respiratory chain. Overexpression of COX5B is associated with a poor prognosis in many cancers [53,54]. The observation that these critical nodes are part of the gene cluster involved in mitochondrial oxidative phosphorylation gains further significance in light of the recent findings that mitochondrial oxidative phosphorylation is upregulated in many cancers including ovarian cancer [55][56][57].…”
Section: Discussionmentioning
confidence: 97%
“…The IHC staining was conducted as described previously [ 14 ]. The recombinant anti-SYNE1 antibody (Abcam, Cambridge, UK, ab192234) was used for SYNE1 staining.…”
Section: Methodsmentioning
confidence: 99%
“…The wound healing experiment was performed by using a wound healing assay kit (Abcam, ab242285) according to the manufacturer’s instructions. The procedures for transwell assay (Corning, Corning, NY, USA, CLS3422) were conducted as previously described [ 14 ].…”
Section: Methodsmentioning
confidence: 99%